2022
DOI: 10.1186/s12870-022-03538-4
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous proline mitigates toxic effects of cadmium via the decrease of cadmium accumulation and reestablishment of redox homeostasis in Brassica juncea

Abstract: Background As a vital osmoticum, proline has an important role in enhancing the tolerance of plants to environmental stress. It is unclear whether the application of exogenous proline can improve the tolerance of Brassica juncea to cadmium (Cd). Results This study investigated the effects of different concentrations of proline (20, 40, 60, 80, and 100 mg/L) under Cd stress at different times (0 d, 2 d, and 7 d) on the growth and physiology of B. ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
3
8
0
Order By: Relevance
“…In plants, Cd toxicity is generally indicated as stunted growth of the root and shoot, chlorosis, and inhibition of photosynthesis [ 37 , 38 ]. In the present study, Cd stress sharply inhibited S. matsudana growth (Tables 1 ), which may have occurred due to the perturbation in cellular processes at the biochemical and physiological levels in plants [ 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, Cd toxicity is generally indicated as stunted growth of the root and shoot, chlorosis, and inhibition of photosynthesis [ 37 , 38 ]. In the present study, Cd stress sharply inhibited S. matsudana growth (Tables 1 ), which may have occurred due to the perturbation in cellular processes at the biochemical and physiological levels in plants [ 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another indicator of the physiological state of plants is the level of accumulation of proline, which performs the function of being an osmoprotectant and an antioxidant [ 48 , 49 ]. Exogenous proline treatment enhanced Brassica juncea ’s tolerance to Cd via a decrease of Cd accumulation and the reestablishment of redox homeostasis [ 50 ]. Proline is an important metabolite for plant adaptation, protection, and tolerance to Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that proline, by helping to maintain the redox balance in the cytoplasm, alleviated the GSH depletion, favoring the synthesis of phytochelatin (see review by X. Liang et al [ 31 ]). In an aside, exogenous proline has been shown to exert an effect on the levels of GSH, increasing the GSH/GSSG ratio in the leaves and roots of B. juncea [ 139 ], validating the indirect effect of proline in stimulating another multifunctional compound, GSH, and strengthening downstream mechanisms of stress tolerance. In fact, Xu et al [ 137 ] suggested that in this way, the conjugation of Cd with phytochelatin would be more easily sequestered in the vacuoles, enhancing the Cd accumulation ability and the phytoremediation potential of these plants [ 137 ].…”
Section: The Involvement Of Proline In Plants Facing Issues Of Soil D...mentioning
confidence: 99%
“…In eggplants ( S. melongena ) exposed to As, the exogenously applied proline seemed to act as an electron donor for PS II [ 143 ]. The CO 2 assimilation rate in metal-stressed plants was also restored upon the addition of exogenous proline by an increase in photosynthetic gas exchange attributes and by enhanced biosynthesis and/or the decreased degradation of chlorophylls and carotenoids [ 139 , 142 ].…”
Section: The Involvement Of Proline In Plants Facing Issues Of Soil D...mentioning
confidence: 99%
See 1 more Smart Citation